Social Media in the Classroom. The New Normal for University Education after COVID - Richardson, Marianna E. (International Dialogues on Education Journal, 2020)
The current pandemic is quickly changing the way professors teach students. In a previous anecdotal study done five years ago, it was difficult finding professors who used social media and online resources effectively in the classroom. With the new normal of online classroom instruction, professors should consider the following three principles as they modify their delivery of information: (1) Instructors should become proficient in using social media and new computer programs before using them in the classroom, (2) social media should be used strategically, not as busy work, and (3) professors should still focus on active learning in their classrooms. The restrictions of social distancing may engender a restructuring of universities. Efficient online institutions may expand their commoditized knowledge delivery while research universities specializing in more specialized, active, hands-on learning finding more creative solutions to fund their institutions.